Kaizen in Japan: transferring knowledge in the workplace. Issue 3 (21st May 2018) - Macpherson, Wayne G.; Lockhart, James C.; Kavan, Heather; Iaquinto, Anthony L.
Abstract : Purpose: As employees in the lower ranks of a Japanese company advance through the levels of management and seniority their role in day-to-day kaizen activities shifts from that of directly improving their own job, operations and surroundings to guiding, educating and facilitating understanding and practice. The emphasis of kaizen to the employee during career progression changes in an embedded, sequential and predictable manner. To a new employee, kaizen is a process to be implemented, something that is visible and largely provided through company training and job manuals, while not necessarily being fully understood. To the senior manager, however, one who has advanced up the corporate ladder, kaizen is tacit knowledge and accumulated experiences, and is seen as being more than just reducing costs, increasing productivity and decreasing lead times. At this point, kaizen becomes something invisible, something that can produce real influence on both the company's profitability and the manager's reputation. Consequently, what kaizen is actually changes from being a duty associated with employment to a matter of personal, group, collective, and organizational responsibility. The purpose of this paper is to explore the mechanism underpinning the transfer of kaizen (acknowledgement and exercise) in the Japanese workplace that results in it being sustained across multiple. Design/methodology/approach: Data were collected from research participants (n = 53) through a mixed-method multi-language field design comprising questionnaires and unstructured interviews conducted in genba, the workplaces of five domain-name multinational companies in Japan. Multi-level statistical analysis identified two largely mutually exclusive generational groups. Findings: During their late 40s, employees were found to transfer their understanding of kaizen between the two forms. At this age, employees were identified to shift from being student to teacher; follower to leader; and disciple to sensei. This study identified how kaizen shifts from one generation to another; when kaizen shifts through the change in responsibility of employees; and changes in the understanding and practice that creates sustained business excellence. Originality/value: Importantly, the study reveals how kaizen itself is a sustainable business activity in the workplace, one that Western business is struggling to emulate.